In vitro flow‐based assay: From simple toward more sophisticated models for mimicking hemostasis and thrombosis. (31st January 2021) - Mangin, Pierre H.; Neeves, Keith B.; Lam, Wilbur A.; Cosemans, Judith M. E. M.; Korin, Netanel; Kerrigan, Steven W.; Panteleev, Mikhail A.; ,
Abstract: In vitro flow‐based assays are widely used to investigate the role of platelets and coagulation in hemostasis and thrombosis. Their main advantage over other assays relies on the fact that they integrate blood flow that regulates many aspects of platelet function, including adhesion, activation, and aggregation. Blood flow is also central in the regulation of coagulation through its ability to modulate the local concentrations of coagulation factors within and around thrombi. The most broadly used assay to study thrombus formation consists in perfusing whole blood over immobilized fibrillar collagen through a single channel, which helps to reproduce thrombus formation as it occurs in vivo after vascular injury, with platelets adhering, becoming activated, and forming a mural thrombus. This process can also be studied under conditions of thrombin generation, notably by recalcifying blood collected in sodium citrate. In this manuscript, we briefly discuss the advantages and limits of this broadly used "in vitro thrombus formation model." The main emphasis is on the description of the most recent developments regarding design of new flow models and new techniques, and how these may advance the landscape of in vitro studies into the formation of physiological or pathophysiological thrombi. Challenges linked to mimicking the formation of a hemostatic plug in a healthy vessel or a thrombus in diseased arteries and the complexity of reproducing the various aspects of venous thrombosis are discussed. Future directions are proposed to improve the physiological or pathophysiological relevance of current flow‐based assays.